Analisis Pengaruh Heat Treatment Terhadap Sifat Mekanik dan Ketahanan Korosi Intergranular SA-240 TP316L - Adhi Setiawan; Puguh Pribadhi; Muhamad Ari (JST (Jurnal Sains Terapan), 2020)
Intergranular corrosion is a problem that often occurs in welding stainless steel materials. Intergranular corrosion is caused by carbide precipitation which occurs at a temperature of 850oC, causing a reduction in chromium content in the Heat Affected Zone (HAZ). The intergranular corrosion process can be controlled by the heat treatment method after the welding process. This study aims to study the effect of heat treatment on mechanical properties and intergranular corrosion resistance of SA240 TP316L material. The variation of heat treatment were divided into three solution treatment (ST), quenching treatment (QC), and non-treatment (NT). Mechanical properties testing using tensile test while corrosion resistance testing using linear polarization using H2SO4 0.1 M solution. Morphology and metal composition in the HAZ area were analyzed using SEM-EDX. Tensile test results showed that welding with solution treatment had the lowest yield strength, ultimate strength, and elongation values compared to specimens of 407.55 MPa, 599.33 MPa, and 44.53%. Corrosion test results found that welding with solution treatment has the lowest corrosion rate compared to specimens with quenching treatment (QC) and non treatment (NT). Corrosion rate in each ST, QC, and NT specimens was 0.90; 1.03; and 2.35 mmpy. The results showed that the solution treatment process can improve intergranular corrosion resistance. Keywords :stainless steel , intergranular corrosion , solution treatment. ABSTRAKKorosi intergranular merupakan permasalahan yang sering terjadi pada pengelasan material baja tahan karat.Korosi intergranular disebabkan oleh presipitasi karbida yang terjadi pada suhu sekitar 850oC sehingga menyebabkan berkurangnya kandungan krom di bagian Heat Affected Zone (HAZ). Proses korosi intergranular dapat dikendalikan dengan metode heat treatment setelah proses pengelasan. Penelitian ini bertujuan untuk mempelajari pengaruh heat treatment terhadap sifat mekanik dan ketahanan korosi intergranular material SA240 TP316L.Variasi heat treatment dibagi menjadi tiga yaitu solution treatment (ST), quenching treatment (QC), dan non treatment (NT). Pengujian sifat mekanik menggunakan tensile test sedangkan pengujian ketahanan korosi menggunakan polarisasi linear menggunakan larutan H2SO4 0,1 M. Morfologi dan komposisi logam pada daerah HAZ dianalisis menggunakan SEM-EDX. Hasil tensile test menunjukkan bahwa pengelasan dengan solution treatment memiliki nilai yield strength, ultimate strength, dan elongation terendah dibandingkan dengan spesimen  yaitu 407,55MPa, 599,33MPa, dan 44,53%. Hasil uji korosi diketahui pengelasan dengan solution treatment memiliki laju korosi terendah dibandingkan dengan spesimen dengan quenching treatment (QC) dan non treatment (NT). Laju korosi pada masing-masing spesimen ST, QC, dan NT sebesar 0,90;1,03; dan 2,35 mmpy.  Hasil penelitian menunjukkan bahwa proses solution treatment dapat memperbaiki ketahanan korosi intergranular.Kata kunci :baja tahan karat , korosi intergranular, solution treatment